Novel Four-Way Slotted-Substrate Integrated Waveguide Power Divider Using Identical Coupling Circuits. Issue 4 (19th May 2017) - Song, Kaijun; Xue, Liyuan; Li, Guoliang; Fan, Maoyu; Fan, Yong
ABSTRACT: A novel four-way X-band slotted-substrate integrated waveguide (SIW) power divider using an identical slot-coupling structure has been proposed in this article. The proposed power divider was realized by using an identical transition between a resonant slotted SIW and output microstrip lines, and four identical rectangular coupling slots were employed to achieve good impedance matching and equal signal transmission. The proposed power divider is designed, fabricated, and measured. The measured results show a reasonable agreement with the simulated ones and the advantages of its low profile, efficient heat sinking, as well as its potential for high power-combining efficiency.